Continuous positive airway pressure for children in resource-limited settings, effect on mortality and adverse events: systematic review and meta-analysis. Issue 6 (8th December 2021) - Sessions, Kristen L; Smith, Andrew G; Holmberg, Peter J; Wahl, Brian; Mvalo, Tisungane; Chisti, Mohammod J; Carroll, Ryan W; McCollum, Eric D
Abstract : Objective: Determine non-invasive ventilation with continuous positive airway pressure (CPAP) outcomes for paediatric respiratory distress in low-income and middle-income countries (LMICs). Design: Systematic review and meta-analysis. Setting: LMIC hospitals. Patients: One month to 15 year olds with respiratory distress. Interventions: We searched Medline, Embase, LILACS, Web of Science and Scopus on 7 April 2020. Included studies assessed CPAP safety, efficacy or effectiveness. All study types were included; neonatal only studies were excluded. Data were extracted by two reviewers and bias was assessed. Certainty of evidence was evaluated, and risk ratios (RR) were produced for meta-analyses. (PROSPERO protocol CRD42018084278). Results: 2174 papers were screened, 20 were included in the systematic review and 3 were included in two separate meta-analyses of mortality and adverse events. Studies suitable for meta-analysis were randomised controlled trials (RCTs) from Bangladesh, Ghana and Malawi. For meta-analyses comparing death or adverse events between CPAP and low-flow oxygen recipients, we found no clear CPAP effect on mortality (RR 0.75, 95% CI 0.33 to 1.72) or adverse events (RR 1.52, CI 0.71 to 3.26). We downgraded the certainty of evidence for both death and adverse events outcomes to 'low' due to design issues and results discrepancies across RCTs. Conclusions: Evidence for CPAP efficacy against mortality and adverse events has low certainty and is context dependent. Hospitals introducing CPAP need to have mechanisms in place to optimise safety in the context it is being used; this includes the location (a high dependency or intensive care area), adequate numbers of staff trained in CPAP use, close monitoring and mechanisms for escalation, daily direct physician supervision, equipment that is age appropriate and user-friendly and continuous monitoring of outcomes and quality of care. Abstract : A systematic review of the efficacy of CPAP in the treatment of pneumonia in children outside the neonatal period in low-and middle-income countries. The effect on patient outcomes is highly context dependent, and the context in which CPAP is safe can be understood from the review - intensive or high dependency care areas where there is close nursing monitoring, regular physician supervision, training for staff in CPAP and pneumonia care, and where other quality improvement processes are in place.